Fracture Mechanics: 26th Volume 1995
DOI: 10.1520/stp16407s
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Fracture Toughness Measurement of Paper

Abstract: Paper sheet material has a high toughness and a low yield stress so that linear elastic fracture mechanics is inappropriate to measure its fracture resistance. Experiments have been conducted on single edge-notched tension SE(T) specimens using the J-integral analysis but there are difficulties in identifying the crack initiation, and the Jc value at 0.2 mm crack growth as required by ASTM E813-89 depends on the slope of the JR-curve which may be affected by specimen size and geometry effects. To overcome thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…2) with different notch sizes, were tested in tension. Following the recommendations of previous authors (Mai et al 1995;Chen et al 2016;Mao et al 2017) the ligaments of the specimens in this research are in the range 6 mm B b 0 B 8 mm, with specimen width (2 W) of 15 mm. Each specimen's ligament was measured using an optical device coupled to a three-dimensional coordinate measuring machine (TESA MICRO-HITE 3D).…”
Section: Fracture Toughnessmentioning
confidence: 95%
See 1 more Smart Citation
“…2) with different notch sizes, were tested in tension. Following the recommendations of previous authors (Mai et al 1995;Chen et al 2016;Mao et al 2017) the ligaments of the specimens in this research are in the range 6 mm B b 0 B 8 mm, with specimen width (2 W) of 15 mm. Each specimen's ligament was measured using an optical device coupled to a three-dimensional coordinate measuring machine (TESA MICRO-HITE 3D).…”
Section: Fracture Toughnessmentioning
confidence: 95%
“…When a test fails to meet the thickness and other test requirements that are in place to ensure plane strain conditions, the fracture toughness value produced is denoted K Q instead of K Ic . The fracture process zone in a piece of paper corresponds to the region just ahead of the crack tip, where the fiber breakage and bond breakage concentrate when a cracked specimen is strained (Mai et al 1995).…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…2) with different notch sizes, were tested in tension. Following the recommendations of previous authors (Mai et al 1995;Chen et al 2016;Mao et al 2017) the ligaments of the specimens in this research are in the range 6 mm ≤ b 0 ≤ 8 mm, with specimen width (2W) of 15 mm. Each specimen's ligament was measured using an optical device coupled to a three-dimensional coordinate measuring machine (TESA MICRO-HITE 3D).…”
Section: Fracture Toughnessmentioning
confidence: 96%
“…When a test fails to meet the thickness and other test requirements that are in place to ensure plane strain conditions, the fracture toughness value produced is denoted K c . The fracture process zone in a piece of paper corresponds to the region just ahead of the crack tip, where the ber breakage and bond breakage concentrate when a cracked specimen is strained (Mai et al 1995). Fracture toughness test were conducted following the K Ic procedure of the standard ASTM E1820-01.…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…Many kinds of mechanical parameters, such as elastic properties, strength, fracture energy, fracture toughness, and post-peak stress-strain curve, are found to be dependent on the size of specimen. For examples, Mai et al (1980) investigated the size effects on fracture load, fracture stress and strain energy density in an asbestos-cellulose cement composite using three point notched bend beams with geometrically scaled dimensions [2]; found that the slope of J Rcurve may be affected by specimen size and geometry effects [3]; Mai (1985) presented the effects of specimen size, geometry and environment on R-curve; Wu and Mai (1996) found that the specific essential work of fracture is a material constant independent of sample geometry, and equivalent to the critical J-integral [4]; Jin and Mai (1995) investigated the size-dependence of thermal shock strength behavior [5]; Cottrell and Mai (1987) used the crack growth resistance curves to explain the specimen size and crack length dependence of fracture toughness in cement pastes [6]; Shah (1990) proposed a size-effect method for determining the fracture energy of concrete by measuring the maximum loads of geometrically similar notched concrete specimens of different sizes [7]; Duan et al (2002) explained the size effect in concrete fracture using nonuniform energy distribution [8]; Bažant and Kazemi (1990) analyzed the dependence of the fracture energy on the specimen size on the basis of Bažant's size effect law [9]; Ji et al (1997) explained the size effect of fracture energy of cement-based materials and a relationship between fracture energy and height of the ligament of specimen was established [10]; Guo and Gilbert (2000) introduced the concept of partial fracture energy to explain the observed size effect [11].…”
Section: Introductionmentioning
confidence: 99%